Exploring Correlates of Loss of Control Eating in a Nonclinical Sample - Conceição, Eva M.; Moreira, Célia S.; de Lourdes, Marta; Ramalho, Sofia; Vaz, Ana Rita (Frontiers in Psychology, 2022)
Objective: Loss of Control (LOC) eating has been directly related to the core aspects of eating disorders’ psychopathology and to different dimensions of emotion and behavior regulation and self-criticism. This study investigates a model representing the interplay between these dimensions to understand LOC eating among a non-clinical sample. Methods: A total of 341 participants recruited in a college campus (mean age 23.21, S.D. =6.02), completed a set of self-report measures assessing LOC, weight suppression, eating disorders’ psychopathology, depression, negative urgency, emotional regulation difficulties, and self-criticism. Path analysis modeling tested a hypothesized model with 3 paths for LOC: 1) eating disorders’ psychopathology; 2) emotion and behavior regulation; 3) interplay between these paths. Results: We found good fit indexes to our data: χ2=17.11, df=10, CFI=.99, TLI=.98, RMSEA=.045, SRMR=.041) suggesting that: 1) participants with higher weight suppression showed higher degrees of eating disorders’ psychopathology, which was linked to higher levels of LOC; 2) Self-criticism was a mediator between emotional regulation and depression/negative urgency; 3) Self-criticism was a mediator between emotion regulation and disorder eating, which was significantly associated with LOC eating via increased negative urgency. Conclusion: Our model shows that LOC eating occurs for individuals with higher eating disorders’ psychopathology who experience depressive symptoms and act rashly under distress for their inability to cope adequately with negative feelings of self-devaluation. These findings point to the importance of negative self-evaluations and feelings of inadequacy or worthlessness to understand LOC eating among college students.